Novel Immunotherapeutic Approaches for Neuroblastoma and Malignant Melanoma. (30th October 2018) - Morandi, Fabio; Frassoni, Francesco; Ponzoni, Mirco; Brignole, Chiara
Abstract : Neuroblastoma (NB) and malignant melanoma (MM), tumors of pediatric age and adulthood, respectively, share a common origin, both of them deriving from the neural crest cells. Although NB and MM have a different behavior, in respect to age of onset, primary tissue involvement and metastatic spread, the prognosis for high stage-affected patients is still poor, in spite of aggressive treatment strategies and the huge amount of new discovered biological knowledge. For these reasons researchers are continuously attempting to find out new treatment options, which in a near future could be translated to the clinical practice. In the last two decades, a strong effort has been spent in the field of translational research of immunotherapy which led to satisfactory results. Indeed, several immunotherapeutic clinical trials have been performed and some of them also resulted beneficial. Here, we summarize preclinical studies based on immunotherapeutic approaches applied in models of both NB and MM.